(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
The study aims to comparative Between the Upper and Lower Limbs of the Quail Fetus , the result showed increases in weight until it reaches maturity . As for monitoring the length of the bird’s body to know that the bird’s body grows in all its organs, then as the length of the body increases, the length of the organs (limbs) increases The growth and development of the limbs appear in the form of lateral swellings in the mesoderm, then the distal end of the limb bud flattens, then rapid growth occurs in the mesoderm cells to gradually turn into cartilage in the limbs, and the cartilage hardens to form the limb bones .